Analysis of the biological control of cassava pests in Africa: II. Cassava mealybug (Phenaccoccus manihoti) - Gutiérrez, A.P.; Neuenschwander, Peter; Schulthess, F.; Herren, H.R.; Baumgaertner, J.U.; Wermelinger, B.; Löhr, Bernhard; Ellis, C.K. (1988)
(1) The effects of the cassava mealybug, Phenacoccus manihoti Mat.-Ferr., on cassava, Manihot esculenta Crantz, growth, development and yields as modified by weather, soil water and nitrogen, and natural enemies were examined. (2) Rainfall-induced mortality and plant carbohydrate stress were the major determinants of P. manihoti population patterns prior to the introduction of exotic natural enemies. (3) The contribution of the introduced parasitoid Epidinocarsis lopezi (DeSantis) and indigenous predators of Hyperaspis and Exochomus to the biological control of P. manihoti was assessed. Native coccinellid predators were not important regulating agents of P. manihoti before the introduction of exotic parasitoids. (4) The contribution of native coccinellids to total P. manihoti mortality appears largely dispensible after the introduction of E, lopezi. (5) The effect of rainfall on density-dependent regulation of P. manihoti by the parasitoid E. lopezi in the field was examined.